Road traffic emission dispersion modelling: an application to Hanoi and Ho Chi Minh city using ADMS. - Ngo, Khoi Quang (Cranfield University, 2020)
Urban air quality in Vietnam has become a pressing matter that require immediate attention to ensure a sustainable development. However due to the overreliance on in-situ observations, which only measure the end result, there is limited understanding of the connection between pollution sources and concentrations. This in turn hinders the effectiveness of environmental law enforcement and management. Since road traffic is widely regarded as the main polluter, attempts have been made to adopt atmospheric dispersion models to traffic emission in Vietnam. Most however, suggest that due to input data scarcity, model applications are limited. This work therefore employed ADMS, an advanced dispersion model that is highly adaptable to produce a full mapping of road traffic derived emission for Hanoi and HCMC, i.e. Vietnam’s 2 most populated cities. Also, a modelling framework, which exploits existing, quality traffic data to generate suitable model inputs, was developed. With this framework, a detailed GIS-based road network dataset that contains road parameters, vehicle count and travel-condition-depending emission factor was produced. Carbon Monoxide was modelled as a pilot pollutant species. Resulted concentrations show an overall moderate positive correlation with observations (r = 0.4). Inadequate information on background pollution however prevents in-depth model validation to be conducted. In overall, this work demonstrates the compatibility of ADMS with the circumstance of Vietnam. Combined with an improved data processing framework, applications of dispersion model in developing countries can be greatly expanded.
Keywords: ADMS; dispersion model; traffic emission; urban air pollution; Vietnam; GIS-based dataset